The influence of manuring on stable isotopes (δ13C and δ15N) in Celtic bean (Vicia faba L.): archaeobotanical and palaeodietary implications - Treasure, E.R.; Church, M.J.; Gröcke, D.R. (Archaeological and Anthropological Sciences, 2016)
This paper examines the impact of animal manure on δ15N and δ13C values in a legume, Celtic Black broad bean (Vicia faba). In a field experiment, V. faba was cultivated in plots treated with farmyard manure and pure sheep manure. The results indicate that highly intensive manuring can increase δ15N values in beans, stems, leaves and pods. In comparison, manuring had a relatively small impact on δ13C values. In terms of palaeodietary reconstructions, the high δ15N values in very intensively manured beans (+3 ‰) are equivalent to the trophic-level effect. Based on the experimental results, it is suggested that high δ15N values in archaeobotanical remains of V. faba may be attributable to small-scale cultivation with intensive manuring.
EPrint Processing Status: Full text deposited in DRO
Keywords: Stable isotopes; Nitrogen; Carbon; Manuring; Legume; Palaeodiet.